Ambiente institucional e a responsabilidade social empresarial na indústria calçadista de Franca: o caso do Instituto Pró-Criança - Alves, Elvisney Aparecido (2007)
The present work approaches the subject of the social responsibility of businesses, considering the implications that the institutional environment exerts on business practices. The business world has increasingly emitted signals acknowledging its social duties, and with regards to Brazil, this has mainly occurred during the last decade of twentieth century. During this period, while taking the shoe industry of Franca as an object of study, the factories social responsibility is manifested in the creation of the Pro-Child Institute as a reaction taken by the local entrepreneurs against allegations of the use of child labor in the productive chain. The transformations verified in the national institutional environment are analyzed in the space of the four classic dimensions of the business social responsibility (economic, legal, ethical and philanthropic), aiming to understand the determining institutions for the phenomenon studied from the point of view of the actors. The perception of the footwear manufacturers associated with the Pro-Child Institute is obtained by means of interviews and survey of the historical declarations registered by the media. The content analysis is made by use of a matrix of thematic categories compatible with the treatment given to the subject of business social responsibility according to the influence of the institutions. The results reveal the preponderant force of economic interests associated with the international market, and the national fragility in the application of the legal measures, in the field of external social obligations, as well as the moral complacency of the actors involved and the restricted contribution of the governing structures toward philanthropic action to transform the local values relative to the use of child labor. The legitimacy of the businesses intermix with the economic interests in the reduction in the costs of transactions and its social representation, as to the relative weight of the institutions that conform to the environment.